2019
DOI: 10.1002/pip.3168
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and modeling of reverse‐bias breakdown in Cu(In,Ga)Se2 photovoltaic devices

Abstract: Partial shading of series‐connected thin‐film photovoltaic modules can force shaded cells into reverse bias, which can cause rapid and irreversible power loss and reduce the practical module lifespan. Unfortunately, this is a common occurrence in field‐deployed modules due to the myriad of environmental factors that can result in partial shading. In this work, we identify as‐grown nonuniformities in the Cu(In,Ga)Se2 (CIGS) absorber layers as the points of origin for the damage induced under reverse‐bias condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
2
11
0
1
Order By: Relevance
“…The current limit of 100 mA was selected because it is the current generated in approximately 3 cm 2 of a neighboring cell that is fully illuminated. Furthermore, this value is in the range of currents (30 -100 mA) observed during the formation of wormlike by Guthrey et al [6].…”
Section: 2mentioning
confidence: 52%
See 2 more Smart Citations
“…The current limit of 100 mA was selected because it is the current generated in approximately 3 cm 2 of a neighboring cell that is fully illuminated. Furthermore, this value is in the range of currents (30 -100 mA) observed during the formation of wormlike by Guthrey et al [6].…”
Section: 2mentioning
confidence: 52%
“…The defect in Figure 4 (a) seems to have originated at the border where the CIGS was mechanically removed (P3 analogue) at the right side of the picture. Several studies [4][5][6][7] showed that wormlike defects originate at local weak spots. A mechanically defined edge could be a local weak spot; though, only 3 out of 8 wormlike defects started at a mechanically defined edge.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…Локальные дефекты от обратного смещения в модулях CIGS часто оптически видимы и имеют вид «червячного следа» [13,14]. Эти дефекты возникают в локальных слабых местах [15,16] и относительно легко распространяются, если не принять меры. Дефекты могут возникать даже за счет тени людей или инструментов при осмотре или очистке панелей [17,18] и могут в стандартных условиях испытаний (STC) вызывать уменьшение максимальной мощности на 10% и более 30% соответственно в случае тени от человека и инструментов для чистки [19].…”
Section: Introductionunclassified
“…Figure 39(b) shows the simulated current density-voltage (J-V) curves for a cell in an ambient temperature of T = 293 K, and 1-sun light. Shunt-induced heating of the cell causes significant Voc loss[68].…”
mentioning
confidence: 99%